2020
DOI: 10.2147/cmar.s223699
|View full text |Cite
|
Sign up to set email alerts
|

<p>The LINC00365/SCGB2A1 (Mammaglobin B) Axis Down-Regulates NF-κB Signaling and Is Associated with the Progression of Gastric Cancer</p>

Abstract: A lack of early diagnostic biomarkers and therapeutic targets has led to poor prognosis for gastric cancer patients. However, the analysis of cancer-associated genomic data has been shown to be effective in identifying potential markers. Recently, the long noncoding RNA LINC00365 and SCGB2A1 gene (as known as mammaglobin B) were predicted to be co-expressed in gastric cancer based on the Gene Expression Omnibus database. However, their precise role in gastric cancer tumors is still not clear. Methods: The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…LINC00365 influences the Wnt/β-catenin signaling pathway, which modulates colorectal cancer (CRC) progression ( 53 ), and breast cancer cell viability may be regulated by the LINC00365-secretoglobin family 2A member 1 (SCGB2A1) axis, which targets NF-κB signaling ( 54 ). In GC, the expression levels of LINC00365 and SCGB2A1 are downregulated in tumor tissues, which is associated with a shorter survival time ( 55 ). Notably, this LINC00365/SCGB2A1 axis and associated NF-κB suppression are associated with GC progression ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LINC00365 influences the Wnt/β-catenin signaling pathway, which modulates colorectal cancer (CRC) progression ( 53 ), and breast cancer cell viability may be regulated by the LINC00365-secretoglobin family 2A member 1 (SCGB2A1) axis, which targets NF-κB signaling ( 54 ). In GC, the expression levels of LINC00365 and SCGB2A1 are downregulated in tumor tissues, which is associated with a shorter survival time ( 55 ). Notably, this LINC00365/SCGB2A1 axis and associated NF-κB suppression are associated with GC progression ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In GC, the expression levels of LINC00365 and SCGB2A1 are downregulated in tumor tissues, which is associated with a shorter survival time ( 55 ). Notably, this LINC00365/SCGB2A1 axis and associated NF-κB suppression are associated with GC progression ( 55 ). In the present study, SOX21-AS1 was demonstrated to be associated with GC in the ceRNA network.…”
Section: Discussionmentioning
confidence: 99%
“…Low LINC00365 expression was closely related to short survival time. In vitro data indicated that LINC00365 up‐regulation suppressed the proliferation ability of gastric cancer cells 15 . By contrast, LINC00365 was up‐regulated in the colorectal cancer, associating with worse outcome of patients.…”
Section: Introductionmentioning
confidence: 96%
“…In vitro data indicated that LINC00365 up-regulation suppressed the proliferation ability of gastric cancer cells. 15 By contrast, LINC00365 was up-regulated in the colorectal cancer, associating with worse outcome of patients. LINC00365 overexpression promoted colorectal cancer cells proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 97%
“…The upregulation of LINC00365, acting as a tumor suppressor, has the potential to serve as a prognostic marker in GC. It suppresses GC cell viability by inhibiting expansion rather than stimulating apoptosis [ 143 ]. Additionally, LINC01235 functions as a prognostic biomarker and facilitates the metastasis of GC cells by inducing EMT [ 144 ].…”
Section: Introductionmentioning
confidence: 99%